Prevention of Venous Thrombo-Embolism in Non-surgical Hospitalized Patients - Indra Putra, Indra Putra; Mutia, Mutia (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the prevention of venous thromboembolism (VTE) in non-surgical hospitalized patients reveals a multifaceted approach to addressing this significant health concern. VTE, which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), is a leading cause of preventable morbidity and mortality within this population. The urgency for effective preventive measures is underscored by the fact that a substantial percentage of hospitalized patients are at risk due to factors such as immobility, obesity, and advanced age (Forgerini et al., 2019). Literature Review: The literature also reveals significant gaps in adherence to prophylaxis protocols. Studies indicate that while evidence-based measures are critical for reducing VTE incidence, adherence remains inconsistent. The need for systematic risk assessment models (RAMs) is emphasized, as these tools can help identify high-risk patients and tailor prophylactic strategies accordingly. Moreover, the literature discusses the importance of integrating clinical decision support systems to enhance the implementation of VTE prophylaxis protocols. Conclusion: In conclusion, the literature underscores the complexity of VTE prevention in non-surgical hospitalized patients, emphasizing the need for improved adherence to prophylactic measures, effective risk assessment strategies, and the integration of clinical decision support systems. The current gaps in practice highlight the necessity for ongoing education and training for healthcare providers, as well as the implementation of comprehensive strategies to enhance patient outcomes and reduce the incidence of VTE.